Surface Integrity of Austenitic Manganese Alloys Hard Layers after Cavitation Erosion - Ion Mitelea; Ilare Bordeașu; Daniel Mutașcu; Corneliu Marius Crăciunescu; Ion Dragoș Uțu (Lubricants)
Cavitation erosion, as a mechanical effect of destruction, constitutes a complex and critical problem that affects the safety and efficiency of the functioning of engineering components specific to many fields of work, the most well-known being propellers of ships and maritime and river vessels, seawater desalination systems, offshore oil and gas drilling platforms (including drilling and processing equipment), and the rotors and blades of hydraulic machines. The main objective of the research conducted in this paper is to experimentally investigate the phenomenology of this surface degradation process of maritime ships and offshore installations operating in marine and river waters. To reduce cavitation erosion of maritime structures made from Duplex stainless steels, the study used the deposition by welding of layers of metallic alloys with a high capacity for work hardening. The cavitation tests were conducted in accordance with the American Society for Testing and Materials standards. The response of the deposited metal under each coating condition, compared to the base metal, was investigated by calculating the erosion penetration rate (MDER) through mass loss measurements over the cavitation duration and studying the degraded zones using scanning electron microscopy (SEM), the energy-dispersive X-ray analysis, and hardness measurements. It was revealed that welding hardfacing with austenitic manganese alloy contributes to an approximately 8.5–10.5-fold increase in cavitation erosion resistance. The explanation is given by the increase in surface hardness of the coated area, with 2–3 layers of deposited alloy reaching values of 465–490 HV5, significantly exceeding those specific to the base metal, which range from 260–280 HV5. The obtained results highlighted the feasibility of forming hard coatings on Duplex stainless-steel substrates.